Facile Synthesis of Pd-Ir Nanocubes for Biosensing - Li, Jiuxing; Li, Yingfu (Frontiers in Chemistry, 2021)
Displaying extremely high peroxidase-like activity and uniform cubic structure enclosed by (100) facets, Pd-Ir nanocubes are an attractive nanomaterial for bioanalysis. However, there exists a great challenge to deposit atomic layers of Ir on the surface of Pd nanocubes due to the relatively low energy barrier of homogeneous nucleation of Ir atoms compared to heterogeneous nucleation. Here, a simple and surfactant-free approach is presented to synthesize Pd-Ir nanocubes with atomic Ir shell thickness in an aqueous solution at room temperature. Biomolecules such as antibodies and nucleic acids have free access to the surface of Pd-Ir nanocubes. Applications of Pd-Ir nanocubes in immunoassays and aptamer-based biosensors are realized, exploiting the excellent peroxidase activity and fluorescence quenching ability of Pd-Ir nanocubes. This work makes a significant step forward towards the practical utility of Pd-Ir nanocubes in bioanalysis.